Single Molecular Machines and Motors Proceedings of the 1st International Symposium on Single Molecular Machines and Motors, Toulouse 19-20 June 2013 - Joachim, Christian; Rapenne, Gwénaël (Advances in Atom and Single Molecule Machines, 2015)
This book brings together different approaches and strategies to design, synthesize and study single molecular machines and motors in a multidisciplinary way. Written by leading international experts, this book summarizes the advances in the field through a number of disciplines. Some contributions describe molecular chemistry such as organic, aromatics, and coordination chemistry while others address theoretical chemistry in a predictive way or through post-experimental modelling. Experimental physics with extensive use of scanning probe microscopy (STM and AFM) is discussed for examining one single molecule. This book is aimed at those who are interested in the rapidly growing field of molecular machines and motors acting and studied at the single-molecule scale. The goal of the authors and editors is to provide the reader with an up-to-date summary while also offering future perspectives on the field.